The Effect of Total Quality Management (TQM) on Customer Satisfaction at UD Fani Mabel Products - Gea, Iman Kasih; Gea, Jeliswan Berkat Iman Jaya; Zai, Kurniawan Sarototonafo; Bate'e, Maria Magdalena (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study investigates the influence of Total Quality Management (TQM) on customer satisfaction at UD. Fani Mabel, a local panglong business in Nias. The research was motivated by persistent challenges, such as inconsistent product quality, delivery delays, and limited responsiveness to customer complaints, which highlight the suboptimal implementation of TQM principles. The objective of this study is to determine whether TQM significantly affects customer satisfaction and to measure the extent of its impact. A quantitative research method with an associative approach was employed, involving a population of 43 individuals consisting of employees and customers. Data collection was conducted through observation and questionnaires using a Likert scale. The data were analyzed using validity and reliability tests, simple linear regression, correlation coefficients, and hypothesis testing with SPSS version 26. The findings indicate that TQM dimensions customer focus, continuous improvement, and employee involvement have a positive and significant influence on customer satisfaction. This suggests that the better the application of TQM, the higher the satisfaction achieved by customers. The study concludes that enhancing consistency in product quality, standardizing production processes, and improving service responsiveness are crucial for achieving sustainable customer satisfaction at UD. Fani Mabel.